Recurring cycles of ice and vegetation on Baffin Island, Nunavut - Martha K. Raynolds; Helga Bültmann; Shawnee A. Kasanke; Gifford Miller; Jonathan H. Raberg (Arctic, Antarctic, and Alpine Research)
Vegetation has recolonized the Arctic numerous times throughout the Holocene. The most recent retreat of glaciers on Baffin Island, Nunavut, has been since the Little Ice Age, due to anthropogenic warming. Retreating cold-based ice often uncovers ancient vegetation. Recently exposed plants can tell us about past plant communities and colonization rates, important information for parameterizing vegetation feedback in climate models. Here, we provide complete descriptions of vegetation communities recently exposed by two retreating ice caps on Baffin Island and compare them with modern vegetation in the surrounding areas. We found that the ancient vegetation was similar to current vegetation, meaning that the current vegetation had not significantly changed during the past several hundred years. Colonization of bare ground was evident and differed depending on the substrate (rock versus finer substrates), with saxicolous lichens colonizing rocks and acrocarpous mosses and liverworts colonizing areas with finer substrates. The mature communities differed at the two sites, mostly because of a warmer climate at the southern site. Vegetation colonization, especially of light-colored rocks, reduces albedo, but the process can take hundreds of years. Changes in plant community composition are likely to continue for thousands of years due to climate change and the arrival of new species.